Cytotoxicity Effect of Methanolic Extract of Aerial Parts of Viburnum punctatum Buch-Ham. Ex D. Don - Renjith Alex, A.; Ilango, K. (Asian Journal of Chemistry, 2011)
The methanolic extract of aerial parts of Viburnum punctatum Buch (AX-M)-Ham. Ex D. Don has been studied for cytotoxicity against human liver cancer cells (HepG2) and human laryngeal epithelial carcinoma (Hep2) and assessed by the tetrazolium (MTT) and sulphorhodamine B (SRB) methods. Methanolic extract of viburnum punctatum (AX-M) showed potent cytotoxicity against HepG2 and Hep2 cells.